Monitoring activity as a teaching-learning tool during academic training in nursing (Research, Society and Development, 2020)
Objective: to report the experience of the monitors in the discipline Nursing in Health of the Elderly of the Nursing Course, referring to the educational actions developed by the academics. Method: Qualitative study, of a descriptive nature of the experience report type lived in a Higher Education Institute. Results and Discussion: the activities were carried out through visits, a work shop about the elderly, conceptualization of the theory of aging and types of violence against the elderly. In view of the experience, it was observed that despite the age, this large portion of the population needs to have the necessary care and not be so stigmatized and a victim of prejudice. Final Considerations: it is inferred that monitoring is an instrument that contributes to the improvement of teaching through new pedagogical experiences that aim at the relationship between theory and practice and mutual participation between students and students.